The Regulatory Transition - Meyer, John R.; Tye, William B. (American Economic Review, 1985)
A number of regulated industries, particularly in transportation and communications, have recently undertaken the transition from a regime of rigid price and entry controls to that of a more competitive market structure. While the different industries have experienced somewhat different fates, the responses to this transition do have certain common underlying characteristics. To start, demands for some form of temporary or continuing regulation during the transition to deregulation can be explained almost entirely as a response to the strength of the entry threat relative to the magnitude of sunk costs incurred by the affected parties in the previous regulatory regime. Where the obstacles to entry are low, the incumbent firms and labor ordinarily seek during the transition to permit them to recover some or all of their sunk costs. When the obstacles to entry are high, customers are likely to make similar demands for protective conditions designed to do the same, particularly when the customers' own sunk costs severely restrict their competitive options after deregulation. Pleas for protective conditions during the transition are widely regarded as introducing market imperfections that should be resisted in the name of regulatory reform. This view, however, naively equates the market results during the transition (when choices are constrained by the presence of sunk costs) to the results that would prevail in a long-run equilibrium where deregulated prices and quantities are established in the absence of most (or any) sunk costs. The regulatory problem during the transition is to define a set of residual (hopefully self-terminating) economic constraints that will satisfy the equity and other considerations created by the shortto medium-term continuation of some sunk costs without creating insurmountable obstacles to approaching an efficient competitive outcome in the long run. Any transition mechanism must thus come to grips with the essence of the transition problem from a political as well as an economic perspective: who is to bear the consequences of the overhang of sunk costs. Note that we are not making a generalized plea for the compensation of losers from deregulation, especially for windfall gains conferred by the regulatory process itself (see Kenneth Gordon, 1981). Rather, the transition problem is defined here to be a limited period in which participants in the regulatory game are permitted to amortize financial commitments made under the prior set of rules while other participants are constrained in their ability to exploit the presence of those sunk costs during the transition. Misunderstanding or failing to recognize this transition problem can pose substantial dangers: specifically, premature application of economic concepts that, while arguably valid in some future regime in which all sunk costs are amortized, decidedly do not account for the effect of these sunk costs on the marketplace in the short run. Misunderstandings of the transition problem may also encourage false conclusions about the eventual results of deregulation, that is, the long-run competitive equilibrium and industry structure that will emerge. As a consequence, policy recommendations designed to address the problems of the transition may tDiscussants: Robert Willig, Princeton University; Thomas Moore, Hoover Institution.